The Liminal Space Between Life and Death in Documentaries - Csilla Peter (Symbolon, 2023)
The concept of liminality is explained and developed by anthropologists and aims to give the reader a closer look on how rituals are conducted in small societies combining everything with something that is based on experience. This paper aims on addressing  the issue of old age, the connection between the passage of time and the gradual degradation of man, but it also focuses on other problems that arise with aging and the transition from life to death. Theoretical approaches are used to explain the use of the observational style in documentary filming when real people’s experiences are followed and then transposed in an observational style into a documentary film. It uses as a case study on my personal observational documentary entitled “You, Margaret” (2021).